Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Cashless Transaction Behavior - Rina Ridarana Sari; Zulfatun Ruscitasari; Suhada Suhada (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
The aim of this study is to determine the impact of financial literacy and lifestyle non-cash transaction behavior among Acehnese students in Yogyakarta. This study used quantitative data and the data sources used were distribution of questionnaires (questionnaires) that have been conducted in July 2022. The population and sample for this study were to 100 Acehnese students in Yogyakarta. The analysis technique used is data analysis technique using descriptive research methods and data analysis with Structural Equation Model (PLS). The results obtained partially indicate that mainly based entirely on results of statistical tests it can be seen that financial literacy affects student behavior in non-cash transaction behavior. From the results of the analysis, known to have a positive effect on Financial Literacy on Non-Cash Transaction Behavior with a positive sign of 0.528 and significant at 5% level or it can be said 1 ,96. From i know the results of the analysis a positive effect on Lifestyle on Non-Cash Transaction Behavior with a positive sign of 0.349 and significant at 5% level or it can be said 1 ,96.